Ferroptosis and myocardial ischemia-reperfusion: mechanistic insights and new therapeutic perspectives - Jin, Binwei; Zhang, Zhiming; Zhang, Yang; Yang, Minjun; Wang, Cheng; Xu, Jiayi; Zhu, Yu; Mi, Yafei; Jiang, Jianjun; Sun, Zhenzhu (Frontiers in Pharmacology, 2024)
Myocardial ischemia-reperfusion injury (MIRI) is a significant factor in the development of cardiac dysfunction following a myocardial infarction. Ferroptosis, a type of regulated cell death driven by iron and marked by lipid peroxidation, has garnered growing interest for its crucial involvement in the pathogenesis of MIRI.This review comprehensively examines the mechanisms of ferroptosis, focusing on its regulation through iron metabolism, lipid peroxidation, VDAC signaling, and antioxidant system dysregulation. We also compare ferroptosis with other forms of cell death to highlight its distinct characteristics. Furthermore, the involvement of ferroptosis in MIRI is examined with a focus on recent discoveries concerning ROS generation, mitochondrial impairment, autophagic processes, ER stress, and non-coding RNA regulation. Lastly, emerging therapeutic strategies that inhibit ferroptosis to mitigate MIRI are reviewed, providing new insights into potential clinical applications.